2022
DOI: 10.1101/2022.02.27.482140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-performance genetically encoded fluorescent indicator for in vivo cAMP imaging

Abstract: cAMP is a key second messenger that regulates diverse cellular functions including neural plasticity. However, the spatiotemporal dynamics of intracellular cAMP in intact organisms are largely unknown due to low sensitivity and/or brightness of current genetically encoded fluorescent cAMP indicators. Here, we report the development of the new circularly permuted GFP (cpGFP)-based cAMP indicator G-Flamp1, which exhibits a large fluorescence increase (a maximum ΔF/F0 of 1100% in HEK293T cells), relatively high b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…However, other studies such as Di Benedetto et al and Lefkimmiatis et al demonstrated that cAMP generated in the cytosol did not enter the mitochondrial matrix, except during mitochondrial permeability transition ( Di Benedetto et al, 2013 ; Lefkimmiatis et al, 2013 ). These different observations might be due to different sensitivities of the indicators used ( Wang et al, 2022 ). For those biological systems in which cytosolic cAMP can enter mitochondrial matrix, further studies are required to dissect the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, other studies such as Di Benedetto et al and Lefkimmiatis et al demonstrated that cAMP generated in the cytosol did not enter the mitochondrial matrix, except during mitochondrial permeability transition ( Di Benedetto et al, 2013 ; Lefkimmiatis et al, 2013 ). These different observations might be due to different sensitivities of the indicators used ( Wang et al, 2022 ). For those biological systems in which cytosolic cAMP can enter mitochondrial matrix, further studies are required to dissect the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum yields were determined using mEGFP as a standard (QY = 0.60). pH titrations were performed by mixing 10 μL concentrated protein solution with 110 μL buffers of different pH ranging from 2 to 11 and the pKa was determined as described previously ( Wang et al, 2022 ). cAMP titrations were performed by mixing 1 μM of purified protein in HEPES buffer with varying concentrations of cAMP (0.001, 0.01, 0.1, 0.5, 1, 2, 5, 10, 25, 100 and 500 μM) or cGMP (0.01, 0.1, 0.5, 1, 2, 5, 10, 25, 100, 500, 1,000 and 2000 μM) and K d and Hill coefficient were determined as described previously ( Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations